2011
DOI: 10.1186/1471-2180-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus from adult and pediatric bathers in marine waters

Abstract: BackgroundStaphylococcus aureus including methicillin resistant S. aureus, MRSA, are human colonizing bacteria that commonly cause opportunistic infections primarily involving the skin in otherwise healthy individuals. These infections have been linked to close contact and sharing of common facilities such as locker rooms, schools and prisons Waterborne exposure and transmission routes have not been traditionally associated with S. aureus infections. Coastal marine waters and beaches used for recreation are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
61
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 30 publications
2
61
1
Order By: Relevance
“…S. aureus (including meticillin-resistant S. aureus) has been recovered from seawater as a result of human bathing activities (Plano et al, 2011). …”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%
“…S. aureus (including meticillin-resistant S. aureus) has been recovered from seawater as a result of human bathing activities (Plano et al, 2011). …”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%
“…Limitations of this method include a minimum processing time of 72 h and technical support to confirm the presence of MRSA in the Staphylococcus-positive wells. However, the current method saves time and is more specific than previously described methods (1,7,11,13,14), and, until an adequate molecular method is found that can distinguish between MRSA and mecA-positive Staphylococcus spp., is an improvement over current methods. Nevertheless, the results of the current study suggest that the Quanti-Tray 2000 MPN approach offers MRSA quantification combined with the increased detection sensitivity of broth enrichment in recreational marine and freshwater samples.…”
mentioning
confidence: 99%
“…There are several potential point and non-point sources, such as recreational bathers (5,11), combined sewer overflows (2), and urban runoff (12), possibly contributing to S. aureus and MRSA loads at recreational beaches. Currently, there is no risk assessment available to provide guidance on levels of MRSA that result in human infection or colonization from contact with contaminated sand or water at marine and freshwater beaches, and more research is needed (11). A key component needed for the development of a risk assessment model is accurate quantification of MRSA from these environments.…”
mentioning
confidence: 99%
See 2 more Smart Citations